2005
DOI: 10.2106/jbjs.c.01630
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of the Knee in Children and Adolescents

Abstract: Integration of patient information with an orthopaedic surgeon's review of the magnetic resonance imaging scan of the knee in children and adolescent patients improves the identification of pathological disorders in four of the six categories evaluated. This study questions the necessity for and appropriateness of a routine interpretation of a magnetic resonance imaging scan of the knee in children and adolescents by a radiologist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 31 publications
0
20
0
1
Order By: Relevance
“…We cannot determine from this study whether the condylar cutoff sign will be useful for diagnosis of incomplete discoid meniscus. Additionally, the difficulty in diagnosing pediatric and adolescent knee problems has been described [11,13]. Kocher et al [11] suggested selective MRI does not provide enhanced diagnostic utility over clinical examination, particularly in children.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot determine from this study whether the condylar cutoff sign will be useful for diagnosis of incomplete discoid meniscus. Additionally, the difficulty in diagnosing pediatric and adolescent knee problems has been described [11,13]. Kocher et al [11] suggested selective MRI does not provide enhanced diagnostic utility over clinical examination, particularly in children.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,33 Based on the current development of various cartilage-specific sequences for improving sensitivity, the status of 3-T MRI as an accurate diagnostic tool, especially for grade III and IV cartilage defects, can be confirmed. 25,30,[34][35][36] von Engelhardt et al 30 reported a uniform (medial, lateral) distribution of grade I/II defects in 3-T MRI examinations. High-grade lesions (grade III/IV) showed a predilection for medial localization.…”
Section: Discussionmentioning
confidence: 99%
“…Most (four) of the seven studies examined the medial femoral condyle; however, some studies also evaluated the lateral femoral condyle, tibia, patella, and trochlea (Table I). Three of the seven studies did not note which articular surface and/or compartment of the knee had osteochondral lesions 14,16,17 . The MRI magnet strengths used in the studies were between 0.35 and 3.0 T. As a result of inconsistencies between imaging techniques and methodological shortcomings of many of the studies, a meta-analysis was not performed.…”
mentioning
confidence: 98%
“…1). Four Level-II 11-14 and three Level-III studies [15][16][17] were included in the final analyses. The results are outlined in Table I.…”
mentioning
confidence: 99%
See 1 more Smart Citation